Morpho-anatomical study of Protium altsonii Sandwith plants (Research, Society and Development, 2022)
This study aimed to describe the morphoanatomical characters of fruits, seeds and seedlings, in addition to characterizing the anatomy of leaves and trunk of the species Protium altsonii Sandwith. The fruits, leaves and wood were collected in the Sustainable Development Reserve in the Iratapuru River (SDR), Amapá. Cross and longitudinal sections were cut with a rotary microtome. As for the characteristics, it was observed that the fruits are globose to ovoid, with a slightly sharp apex and short stipitate, and they also present one and, more rarely, two pyrenes per fruit. The mature seed of P. altsonii, in cross section in the abaxial region, is formed by the seed-coat with collapsed cells and fleshy cotyledonary parenchyma, containing secretory cavities and oil. In understory, the leaves of young plants with two years and six months are compound, imparipinnate and can present 6 to 11 pairs of leaflets. In their turn, the adult leaves are compound, imparipinnate and may present six or more pairs of leaflets per branch. In a cross-section of the wood, there are numerous solitary and multiple vessels; small to medium; vascular elements with a simple perforation plate. The morphological characteristics of the fruit, seed and leaves, in addition to the anatomy of the species under study allow us to assure that Protium altsonii presents phenotypic plasticity as an ecological strategy. The germinative efficiency in field of these species may have been caused by the release of the coumarin present in the cotyledons.